Performance evaluation of a novel solar air heater with arched absorber plate. (December 2017) - Singh, Simarpreet
Abstract: The study presents a performance evaluation of a novel solar air heating system with arched absorber plate using turbulators. Simulation work is carried out in ANSYS FLUENT (v16.2) platform with RNG k-ε turbulence model at constant heat flux (500 W m −2 ), in order to compare the thermal-hydraulic performance of the proposed design for a range of Reynolds number (3800–14000). Performance of the solar air heater is projected in the terms of Nusselt number ( Nu ), frictional factor ( Fr ) and thermal-hydraulic performance parameter ( THPP ). It is observed that the arched absorber plate design increases the air turbulence and vortex generation, which results in reducing laminar sub-layer generation near the surface of the absorber plate. A significant improvement is observed in Nusselt number at high Reynolds Number (above 10000). However, a marginal enhancement is also observed in frictional factor due to providing an extra obstacle along the duct length with arched shaped design in the flow field. It is observed that arched shape design of absorber plate can significantly improve overall performance of the solar air heating system using various turbulators. This study will likewise provide a new direction to the work trend in this area. Highlights: Solar air heater design with arched absorber plate is proposed and a comparative study is made using plane, triangular and dimply turbulators. Significant improvement is observed in Nusselt number at high Reynolds number (above 10000). A marginal enhancement in the frictional factor is also observed and which reduces further at high Reynolds number (above 10000).